Denial among cancer patients. Tips and traps. - Brock, G. (College of Family Physicians of Canada, 1993)
The coping mechanisms used by patients diagnosed with cancer play a role in their well-being and, therefore, influence their quality of life and possibly even their survival. We review the characteristics of one of these mechanisms, denial, and suggest an approach to dealing with denying patients.